McCune-Albright syndrome without endocrine dysfunction: Case report in a young boy - Sami, Elkashif; Pankaj, Agrawal (Indian Journal of Child Health, 2017)
The McCune-Albright syndrome (MAS) is a sporadic rare disease characterized by a triad of physical signs: Café-au lait spots, polyostotic fibrous dysplasia, and autonomous endocrine hyperfunction. Based on the studies, it can be concluded that this syndrome is caused by mutations that happen in the gene: GNAS1. A small number, but not all, of the patient’s cells contain this faulty gene (mosaicism). MAS is predominantly observed in girls and is rarely reported in males. We report a 5-year-old boy with café-au-lait spots, polyostotic fibrous dysplasia, and without any endocrine dysfunction.